Hyperspherical close-coupling calculations for electron-capture cross sections in low-energy Ne10++H(1s) collisions - Barragán, Patricia; Le, Anh-Thu; Lin, C. D. (My University, 2006)
We present total and partial electron-capture cross sections for Ne10++H(1s) collisions at energies from 0.01eVto1keV using the hyperspherical close-coupling method. Good agreements with the previous calculations by the classical-trajectory Monte-Carlo method are found for total capture cross section, but not for partial cross sections, especially below about 200eV∕amu. We found that the total cross section is mainly due to the population of n=7 channels and only at energies above 50eV∕amu n=5,6 channels begin to contribute to the total cross section.